‘Estates’ or ‘forts’ in Persian period Yehud? - Ḳlẹter, Raz (Palestine exploration quarterly, 2021)
A series of large Persian Period buildings dots the Judean Mountains; they are usually located alone in prominent places without nearby villages or other remains. Their presence stresses the scarcity of towns and villages in Yehud. In a recent article in this journal, Faust, A. (2018. ‘Forts or agricultural estates? Persian period settlement in the territories of the former Kingdom of Judah’, PEQ 150/1, 34–59) noted difficulties with the interpretation of these buildings as forts. He suggested that they were estates, and that their ‘settlers’ were Judean or Jewish returnees from Babylonia. Moving this discussion forward, we stress that the archaeological data does not furnish clear answers, mainly since functions of ‘forts’ and ‘estates’ are not mutually exclusive. Such buildings are not limited to Yehud: they appear also in Idumea, Samerina, and Transjordan. An estate is not a certain type of building that can be easily identified by archaeologists, but a set of land rights and obligations. The variety of Persian Period forms of land tenure should be acknowledged. We suggest that these buildings served more than one function. Perhaps some of those living in them followed haṭru-like arrangements (thus Faust), but if so, they were colonial settlers in the service of Persia, who received their land from the king or satrap, rather than free persons returning to their ancestral lands. They also did not remain there for long, since the phenomenon of the buildings was limited in duration and numbers of dwellers. The buildings did not develop into larger settlements; most were abandoned and did not continue into the Hellenistic Period.